GENDERLECT ASPECTS IN COUNTRY SONGS: A PRAGMATIC STUDY - Ardia Garini; Mualimin Mualimin (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
A song can be sung by both female and male singers, but some are not. It depends on how the songwriter creates the music lyrics. The songwriter’s gender can also influence the use of the communication style of the lyrics. It is because the way communication between males and females is as different as a culture, appropriates with the term of Genderlect. The goal of this study is to determine the influence of genderlect and the indication of the gendered song in country songs. The data used are country song nominees of Grammy Music Awards 2020. The data are analyzed by presupposition analysis and this study uses purposive sampling and non-participant observation methods for collecting the data. The result of the study shows that genderlect influences the gender of the songwriter, on producing the language of the lyrics. Meanwhile, for the gendered song, it is indicated by the singer who sings the lyrics or the language of the song. Keywords: genderlect; gendered country song; presupposition analysis